Anniversary meeting: 30 November 1922 (Proceedings of the Society of Antiquaries of Scotland, 1923)
The usual business was conducted at the Anniversary meeting, including the election of new Fellows and the presentation of a list of deceased Fellows. Other reports presented included: A report on the number of Fellows on the Society’s Roll Brief obituaries for some of the Fellows who died in the previous yearA report on the progress of the Society’s forthcoming publicationsA report on the items added to the Society’s museum and library collections over the previous sessionA report on the Society’s excavations in ScotlandA note on the Rhind LecturesTreasurer then presented the Annual Report on the Society’s finances. Meeting notes for 11 December, 1922 are appended.